Colombian rural women as a vulnerable group within the framework of the law on victims and land restitution. Law 1448 of 2011 - Arango Delgado, Angie Valentina (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2021)
This paper proposes to explain, based on the methodology proposed by the European Commission in the “Gender Mainstreaming Manual”, why rural women victims of the armed conflict in Colombia are a particularly vulnerable group and what are the main barriers they face when claiming their right to land restitution, specifically in the programmes that are being developed within the framework of Law 1448 of 2011.